mrkA, mrkD, AND fimH BIOFILM GENES DETECTION: A STUDY ON Klebsiella pneumoniae CLINICAL ISOLATES - ‘Ariqah ‘Azizah, Intan; Mardhia, Mardhia; Fajar Liana, Delima; Mahyarudin, Mahyarudin (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2025)
Biofilm formation is a virulence factor contributing to the pathogenicity and antibiotic resistance of Klebsiella pneumoniae. This process occurs due to biofilm genes in clinical isolates, especially the mrkA, mrkD, and fimH genes. These three genes are related the quality of biofilms formed, which lead to chronic and prolonged infections. This study was conducted to determine the presence of mrkA, mrkD, and fimH genes as biofilm formers in Klebsiella pneumoniaeclinical isolates. The study used a descriptive in vitro laboratory study, with total of 24 Klebsiella pneumoniae clinical isolates from the collection of the Department of Microbiology, Faculty of Medicine, Universitas Tanjungpura. Isolates were subculture in MacConkey Agar, Gram staining, followed by DNA extraction and gene detection using PCR. The results showed the presence of the mrkA gene in 91.6% of the isolates, while the mrkD and fimH genes were each in 87.5% of the isolates. The high percentage of biofilm gene detected, should increase health workers and stakeholder awarness about the impact.